1991
DOI: 10.1084/jem.174.6.1425
|View full text |Cite
|
Sign up to set email alerts
|

Immune response against lymphocytic choriomeningitis virus infection in mice without CD8 expression.

Abstract: SummaryThe immune response against lymphocytic choriomeningitis virus (LCMV) was studied in a mutant mouse strain that does not possess CD8 § T lymphocytes. Virus-specific cytotoxic T cell activity was generated in spleens of wild-type mice in an acute LCMV infection but was not measurable in mutant mice. Injection of replicating LCMV into footpads of wild-type mice induced a CD8 + T cell-mediated swelling that peaked on day 8, followed by a CD4 + T cell-mediated swelling that peaked on day 11, whereas mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 28 publications
7
136
2
Order By: Relevance
“…Secondly, we have demonstrated that, in an anti-allogeneic response, cytotoxicity is mostly conserved, and the absence of CD8 expression in patients impairs the cytotoxic capacity of the DN T cells to a moderate extent. This is in agreement with the normal cytotoxicity responses observed in CD8 knockout mice [24][25][26] and is shown in humans for the first time in the present work. Third, the high antibody titers to several viral infections in the patients 15 demonstrate that they have been in contact with those viruses and have been immunocompetent enough to beat the infections.…”
Section: Discussionsupporting
confidence: 93%
“…Secondly, we have demonstrated that, in an anti-allogeneic response, cytotoxicity is mostly conserved, and the absence of CD8 expression in patients impairs the cytotoxic capacity of the DN T cells to a moderate extent. This is in agreement with the normal cytotoxicity responses observed in CD8 knockout mice [24][25][26] and is shown in humans for the first time in the present work. Third, the high antibody titers to several viral infections in the patients 15 demonstrate that they have been in contact with those viruses and have been immunocompetent enough to beat the infections.…”
Section: Discussionsupporting
confidence: 93%
“…Although we found that the levels of total CD3 + CD8 + T cells were similar in the two strains of mice post CVB5 infection, we showed that in the absence of T1/ST2, there was a significant reduction in the number of IFNg-and TNF-a-producing CD3 + CD8 + T cells, which have been implicated in a range of antiviral activities (33,34). This is consistent with a recent report indicating that IL-33 could drive protective antiviral CD8 + T cell responses during LCMV infection in mice (35).…”
Section: Discussionmentioning
confidence: 73%
“…T he clearance of many viral infections, including hepatitis B virus (HBV), 3 requires the effector functions of CD8 ϩ CTLs (1,2). These effector functions include secretion of cytokines, such as IFN-␥ and TNF-␣, as well as cytolytic activity mediated by perforin and granzyme B (3)(4)(5).…”
Section: Pd-1:pd-l1 Interactionsmentioning
confidence: 99%